Flashcard Development to Improve Learning Outcomes in Private 4th Class Science Learning - Riris Fitriyani; Elok Fariha Sari (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop flashcard products equipped with barcodes, test the feasibility of flashcard media in science learning to improve student learning outcomes; and knowing the effectiveness of using flashcard media in increasing average scores. This type of research is Research and Development (R&D) using the Borg & Gall development model which includes eight stages, namely potential and problems, gathering information, product design, design validation, design improvement, product testing, product revision, and usage trials. The subjects of this research were fourth grade students at SDN 01 Bojongkoneng. The research results showed: Flashcard learning media, product validity as seen from the validation results by material expert validators got a percentage of 90%, and media experts got a percentage of 92%; The effectiveness of the product can be seen from the results of student responses which include small group trials getting an average pretest score of 54 and posttest 82, and large group trials getting an average pretest score of 51 and posttest 85. In the small class the score is n- the gain was 0.60 in the medium category, while the large class obtained an n-gain value of 0.68 in the medium category. Thus, the research results show that learning media in the form of flashcards and equipped with barcodes is feasible and effective in learning science and technology as an improvement in student learning outcomes.